Breastfeeding duration and neurodevelopment: insights into autism spectrum disorders and weaning practices - Budor H. Saigh (Journal of Health, Population and Nutrition)
Abstract This paper examines the complex relationship between breastfeeding duration and the incidence of autism spectrum disorders (ASDs), focusing on identifying the most beneficial weaning period and its subsequent effects on child development. Breastfeeding is widely recognized for its role in promoting early health, strengthening the immune system, and supporting neurodevelopment. However, the debate over its optimal duration persists. Integrating insights from current scientific studies with interpretations of Qur’anic teachings, this study advocates for a breastfeeding duration of 21 months. This duration balances the benefits of extended breastfeeding with potential risks associated with prolonged exposure, reflecting both ancient wisdom and contemporary evidence. Key findings suggest that breastfeeding may play a preventive role in mitigating ASD symptoms and enhancing neurodevelopment through mechanisms such as immune regulation, microbiome diversity, and hormonal pathways. These insights underline the need for further specialized research to explore the long-term impacts of breastfeeding on ASD-related outcomes.